Laparoscopic Treatment of Large Adrenal Tumor is Safe and Effective? A Single Center Experiences. Issue 9 (19th August 2021) - Zhao, Juping; Ma, Wenming; Xie, Jialing; Dai, Jun; Huang, Xin; Fang, Chen; He, Wei; Sun, Fukang
Abstract: Background: The comparisons between open surgery and minimally invasive surgery for treatment of large adrenal tumor (LAT) are still lacking. In this study, we attempted to explore the safety and effectiveness of laparoscopic treatment of LAT by comparing the outcomes between open adrenalectomy (OA) and laparoscopic adrenalectomy (LA). Methods: From 2003 to 2018, 78 LAT patients underwent tumor resection by OA or LA method at a single academic institution. Data were retrospectively collected and analyzed. Results: The median largest diameter of LAT was 10.0 (IQR 9.0–13.4) cm. The median operation time in OA group was 215 (IQR 180–240) min versus 180 (IQR 135–245) min in LA group ( P  = 0.042). The median blood loss in OA group was 1000 (IQR 625–1500) ml versus 200 (IQR 100–700) ml in LA group ( P  < 0.001). The median Clavien–Dindo score in OA group was 2 (IQR 2–4) versus 0 (IQR 0–4) in LA group ( P  = 0.035). On univariate and multivariate analysis, the largest diameter of tumor was significantly associated with operation time, blood loss, and recovery time ( P  < 0.05). Conclusions: Laparoscopic treatment of LAT was found to be safe and feasible in experienced hands and can replace open surgeries in most cases.